Characterization of monoclonal antibodies against porcine epidemic diarrhea virus S1/S2 junction protein - Nan Huang; Qiaoli Lang; Liping Li; Liangpeng Ge; Xi Yang (AMB Express, 2023)
Abstract Pig producers have faced considerable economic losses due to porcine epidemic diarrhea virus (PEDV) infection, emphasizing the need for PEDV antibody development. The S1/S2 junction (S1S2J) cleavage site of the S protein of PEDV is one of the major determinants of coronavirus infection success. In this study, we specifically selected the S1S2J protein of PEDV-AJ1102 (a representative strain of the G2 type) as a target protein to immunize mice and generated monoclonal antibodies (mAbs) using hybridoma technology. Three mAbs with high-binding activities to the S1S2J protein and were obtained and further analyzed. To reveal the characterization of these mAbs, variable region genes of antibodies were studied by using DNA sequencing, thereby revealing differences in their CDR3 amino acid sequences. We then developed a new method to identify the isotypes of these three mAbs. Results showed that these three antibodies were of the IgM type. As for the functions of these three mAbs, indirect immunofluorescence assay confirmed their good binding ability to Vero E6 cells infected with the PEDV-SP-C strain (G1 type). Epitope analysis showed linear epitopes for all three mAbs. These antibodies were also used to detect infected cells via flow cytometry analysis. In summary, we prepared and examined three mAbs against PEDV-S1S2J. These mAbs can be employed as detection antibodies for diagnostic reagents and further developed for other applications. We also designed a novel technique for easy and cost-saving identification of isotypes of mouse mAbs. Our results lay a good foundation for the development of research on PEDV.